1975
DOI: 10.1007/bf00616415
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics in the elderly

Abstract: The pharmacokinetics of sulphamethizole, paracetamol and phenylbutazone were investigated and compared in young and geriatric subjects. The rate and extent of absorption of the drugs did not appear to be affected by increasing subject age. However, the mean half-lives for sulphamethizole and paracetamol were significantly increased in the geriatric subjects. A number of correlations are presented between the elimination rate constants of the drugs and certain subject parameters and variables. The elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
3

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(47 citation statements)
references
References 18 publications
5
39
3
Order By: Relevance
“…For instance, glomerular filtration rate and renal plasma flow fall by about 3 5% between the third and eighth decades (Davies & Shock, 1950). Examples of other drugs which have been shown to be excreted more slowly in the elderly and where the kidney plays a major or exclusive role in elimination are benzylpenicillin (Molholm-Hansen, Kampmann & Laursen, 1970), digoxin (Ewy, Kapadia, Yao, Lullin & Marcus, 1969), kanamycin (Kristensen, Molholm-Hansen, Kampmann, Lumholz & Siersback-Nielsen, 1974) and sulphamethazole (Triggs, Nation, Long & Ashley, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, glomerular filtration rate and renal plasma flow fall by about 3 5% between the third and eighth decades (Davies & Shock, 1950). Examples of other drugs which have been shown to be excreted more slowly in the elderly and where the kidney plays a major or exclusive role in elimination are benzylpenicillin (Molholm-Hansen, Kampmann & Laursen, 1970), digoxin (Ewy, Kapadia, Yao, Lullin & Marcus, 1969), kanamycin (Kristensen, Molholm-Hansen, Kampmann, Lumholz & Siersback-Nielsen, 1974) and sulphamethazole (Triggs, Nation, Long & Ashley, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Re-shown that some NSAIDs (e.g. benoxaprofen, duced metabolism of some drugs also occurs phenylbutazone) have altered disposition in the elderly (Hamdy et al, 1982;Triggs et al, 1975). Other drugs however such as indomethacin and fenbufen show little change in their pharmacokinetics (Crooks et al, 1983;Braverman, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Of more importance is the impairment of renal function in old age, causing increased plasma concentrations of drugs which are excreted by the kidney (Crooks et al, 1976). A change in apparent volume of distribution (Nation, Learoyd, Barber & Triggs, 1976) and diminished activity of metabolising enzymes in the liver may also be involved (Triggs, Nation, Long & Ashley, 1975;Reynolds, Wilson & Burnett, 1978). Obviously, more than one of these factors may be responsible for the changes in pharmacokinetics noted in the elderly.…”
Section: Introductionmentioning
confidence: 99%